Mechanism of Fumaric Acid Accumulation in Rhizopus nigricans - Romano, Antonio H. (1967)
It is doubtful that the glyoxylate bypass plays a significant role in the accumulation of fumaric acid by fungi, as has been postulated. In high glucose media, which favor fumarate production, isocitrate lyase (threo-D(s) isocitrate glyoxylate lyase), which is the key enzyme of the glyoxylate bypass, is strongly repressed. The specific activity of this enzyme remains low as long as glucose is present in the medium, even though fumarate formation proceeds at a high level. In addition, the activity of isocitrate lyase is inhibited by phosphoenolpyruvate, which would be formed from glucose. Alternatively, evidence is presented that bulk accumulation of fumaric acid under aerobic conditions in high glucose media takes place through a C(3) plus C(1) carbon dioxide fixation. CO(2) fixation was measured by the direct incorporation of NaHC(14)O(3) into fumaric acid, and by demonstrating that the specific radioactivity of fumaric acid formed from uniformly labeled C(14)-glucose was decreased in the presence of nonradioactive carbonate. The extent of decrease in specific radioactivity is in accord with a C(3) plus C(1) CO(2) fixation mechanism.